RANTAI PASOK MATERIAL PADA INDUSTRI GALANGAN KAPAL - Vita Rumanti Kurniawati; Triwilaswandio W. P. (Buletin PSP, 2008)
Fishing vessel regeneration was barrier by high cost and late delivery. In the mean time, procurement activity influence production cost and on time delivery. Therefore efficiency in material supply chain keep cost and accelerate ship production. One of supply chain performance indicator is delivery performance. This capability depend on shipyard supply chain management in the procurement activity. Purpose of this research is analyze of material supply chain management. General problem of supply chain management is long lead time and material delay. Fluctuation material lead time depend on material specification, buying mechanism, manufacture lead time, supplier location, transportation, finance condition, and delay situation. Delay can happen because mistake of shipyard, supplier, forwarder, customs, and transportation service. The reduction of material lead time can be obtained through direct buying mechanism, using local component, and credit guarantee from national banking. Whereas, delivery delay can be anticipated through earlier purchasing, cooperation with national banking and internal integration of design, procurement and production activity.